Mainstreaming gender dimensions in water management for food security - Abdellatif M. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
Women's role in water management is vital as they are the real custodians of the family's water requirements. They are involved in irrigated agriculture either by way of assisting their husbands or families. In spite of this, water resources management and irrigation programmes and projects are mostly directed to men and to the crops they grow. Promotion of gender equity in water management presupposes an entire set of changes in the actual conceptual framework that still fails to see women as true economic actors and resource managers. In spite of women's major role in Palestinian rural areas in the development process, most of their work falls within the type of work that is without a direct cash wage and within the scope of the informal sector. Studies show that women's work in agricultural field become representing about 80 percent in Palestinian villages.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)